Inheritance of tolerance to high temperature at anthesis in rice - S. Sukkeo (2018)
© Society for the Advancement of Breeding Research in Asia and Oceania (SABRAO) 2017. The problem of high temperature in rice in the tropics is exacerbated by climate change. Anthesis is the stage when rice is most sensitive to high temperature stress, understanding genetic control of the tolerance should contribute to efforts to adapt the rice plant to global warming. This study examined how heat tolerance at anthesis of the progeny of a cross between a tolerant and sensitive parent was inherited through the F1, F2 and F3 generations. Raising anthesis temperature from 32 o C to 38 o C decreased pollen viability and spikelet fertilization in the sensitive parent but had no effect on pollen viability and less severe depression on the percentage of fertilized spikelets of the tolerant parent and the F1 hybrids, in either of the reciprocal crosses. A pattern of transgressive segregation of spikelet fertilization under high temperature that was skewed towards the tolerant parent was observed in the F2 and F3 populations subjected to 37-38 o C at anthesis. It is concluded that high temperature tolerance during anthesis is controlled by complete dominance with a complexity of genes. Identification of the relevant genes and molecular markers associated with the tolerance should enable the trait to be deployed in rice breeding programmes. The dominant gene action suggests that the progeny testing would be essential during selection.